2005
DOI: 10.1126/science.1109389
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Addition of Ammonia to Form a Stable Monomeric Amido Hydride Complex

Abstract: The insertion of an iridium complex into an N-H bond in ammonia leads to a stable monomeric amido hydride complex in solution at room temperature. This reaction advances the transition-metal coordination chemistry of ammonia beyond its role for more than a century as an ancillary ligand. The precursor for this insertion reaction is an iridium(I) olefin complex with an aliphatic ligand containing one carbon and two phosphorus donor atoms. Kinetic and isotopic labeling studies indicate that olefin dissociates to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
294
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 429 publications
(307 citation statements)
references
References 21 publications
8
294
0
5
Order By: Relevance
“…It is also worth noting that the substrates cope of such compounds includes molecules such as ammonia,which hashistorically provendifficult to activate using precious metalc atalysts due to the unfavourable coordination/activation equilibrium. Newr outes resultingi nt he activation of NÀHb onds in ammonia are particularly appealing, becauseo ft he dearth of transition-metal systems capable of effecting such at ransformation, [7][8][9][10][11][12][13][14][15][16][17][18][19] and the relevance of NÀHa ctivation to an umber of potentially important industrialp rocesses. [20] More recently,g eometrically constrained compounds based on phosphorus(III) have also received significant attention in this field.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that the substrates cope of such compounds includes molecules such as ammonia,which hashistorically provendifficult to activate using precious metalc atalysts due to the unfavourable coordination/activation equilibrium. Newr outes resultingi nt he activation of NÀHb onds in ammonia are particularly appealing, becauseo ft he dearth of transition-metal systems capable of effecting such at ransformation, [7][8][9][10][11][12][13][14][15][16][17][18][19] and the relevance of NÀHa ctivation to an umber of potentially important industrialp rocesses. [20] More recently,g eometrically constrained compounds based on phosphorus(III) have also received significant attention in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Although many factors control the kinetics and the thermodynamics of the coupling reaction, the relative stability can be affected by the electron density at the metal center. 2 The strongly electron donating ligand [Cy-PSiP] favored the amido hydride complex over the ammonia complex. 4 The coordination of ammonia would transfer considerable amount of electron density to the already electron-rich metalcenter in the presence of other electron donating ligand.…”
mentioning
confidence: 99%
“…For example, the insertion of an Ir complex into an N-H bond in ammonia forms a stable amido hydride complex in solution at room temperature. 2 Recently, a report showed that Ir complexes supported by silyl pincer ligands undergo an N-H bond oxidative addition for both ammonia and aniline, which forms isolable [Cy-PSiP]Ir(H) (NHR) (R = H, or aryl;…”
mentioning
confidence: 99%
See 2 more Smart Citations